How to p aint landscapes quickly and beautifully in watercolor and gouache - Fowkes, Nathan ([Culver City, California] : Design Studio Press, 2019)
How to Paint Landscapes Quickly and Beautifully with Watercolor and Gouache reveals quick and effective painting setups and techniques to depict any landscape. From simplifying complex scenes and making smart choices about portraying light and texture, to establishing an effective color palette to enhance mood, world-renowned entertainment and fine artist Nathan Fowkes shares priceless lessons that he has developed over twenty five yearsof painting a broad range of places. His detailed tutorials and thoughtful insights will help you create more impactful, gallery-worthy landscapes on locationwithout an easelin record time.
Materials -- Using the materials -- The simple statement -- Light and value -- Edges and textures -- Color: limited palette -- The design of color -- Depth -- Composition -- Putting it all together -- Recommended exercises -- Gallery of paintings.
Keywords: Watercolor painting -- Technique; Landscape painting -- Technique